Model Komunikasi Sosial Pemerintah Daerah dalam Pemberdayaan Ekonomi Pedagang Kaki Lima (PKL) di Jombang - Muchlis; Elok Maria Ulfah; Ariza Qurrata A’yun (Jurnal Komunikasi Nusantara, 2025)
This study aims to analyze the social communication model implemented by the local government in the economic empowerment of street vendors (PKL) in Mojoagung Park and Dr. Soetomo Street, Jombang Regency. The study used a qualitative approach with a descriptive-exploratory design. Data were collected through in-depth interviews, participant observation, and document review, and validated using source and method triangulation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results show that the government's social communication model is a strategic process that includes goal setting, audience segmentation, message development, communication channel selection, strategy implementation, and evaluation and monitoring. The implementation of the model faces various obstacles, including limited resources, regulatory issues, limited infrastructure, social inequality, and uneven participation of street vendors. Nevertheless, street vendors' responses to the government's social communication model tend to be positive, as reflected in increased trust in the government, involvement in the decision-making process, and direct impacts on business activities. These findings emphasize the importance of participatory and sustainable development communication in efforts to empower the informal sector economy. Abstrak Penelitian ini bertujuan menganalisis model komunikasi sosial yang diterapkan oleh pemerintah daerah dalam pemberdayaan ekonomi pedagang kaki lima (PKL) di Taman Mojoagung dan Jl. Dr. Soetomo, Kabupaten Jombang. Penelitian menggunakan pendekatan kualitatif dengan desain deskriptif-eksploratif. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan telaah dokumen, serta divalidasi menggunakan triangulasi sumber dan metode. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa model komunikasi sosial pemerintah merupakan proses strategis yang mencakup penentuan tujuan, segmentasi audiens, pengembangan pesan, pemilihan kanal komunikasi, implementasi strategi, serta evaluasi dan pemantauan. Implementasi model menghadapi berbagai kendala, antara lain keterbatasan sumber daya, persoalan regulasi, keterbatasan infrastruktur, kesenjangan sosial, serta partisipasi PKL yang belum merata. Meskipun demikian, respons PKL terhadap model komunikasi sosial pemerintah cenderung positif, yang tercermin dari meningkatnya kepercayaan terhadap pemerintah, keterlibatan dalam proses pengambilan keputusan, serta dampak langsung terhadap aktivitas usaha. Temuan ini menegaskan pentingnya komunikasi pembangunan yang partisipatif dan berkelanjutan dalam upaya pemberdayaan ekonomi sektor informal.